Biological Control of Plant-Parasitic Nematodes by Filamentous Fungi Inducers of Resistance: Trichoderma, Mycorrhizal and Endophytic Fungi - Poveda, Jorge; Abril-Urias, Patricia; Escobar, Carolina (Frontiers in Microbiology, 2020)
Plant-parasitic-nematodes represent a major threat to the agricultural production of different crops worldwide. Due to the high toxicity of chemical nematicides, it is necessary to develop new control strategies against nematodes. In this respect, filamentous fungi can be an interesting biocontrol alternative. The genus Trichoderma, mycorrhizal and endophytic fungi are the main groups of filamentous fungi studied and used as biological control agents (BCAs) against nematodes as resistance inducers. They are able to reduce the damage caused by plant-parasitic nematodes directly by parasitism, antibiosis, paralysis and by the production of lytic enzymes. But they also minimise harm by space and resource-competition, by providing higher nutrient and water uptake to the plant, or by modifying the root morphology, and/or rhizosphere interactions, that constitutes an advantage for the plant-growth. Besides, filamentous fungi are able to induce resistance against nematodes by activating hormone-mediated (salicylic and jasmonic acid, strigolactones among others) plant-defence mechanisms. Additionally, the alteration of the transport of chemical defence components through the plant or the synthesis of plant secondary metabolites and different enzymes can also contribute to enhancing plant defences. Therefore, the use of filamentous fungi of the mentioned groups as BCAs is a promising durable biocontrol strategy in agriculture against plant-parasitic nematodes.